Prevalence of Metabolic Syndrome in Adult Population from Zahedan, Southeast Iran - MA Kaykhaei; M Hashemi; B Narouie; A Shikhzadeh; M Jahantigh; E Shirzaei; B Rezazehi; M Hoseinian; S Yousefi; S Masoudian; A Emamdadi; SF Alavi; et al. (Tehran University of Medical Sciences, 2012)
Background: The metabolic syndrome (MES) is associated with a high risk of diabetes and cardiovascular disease. The aim of the present study was to determine the prevalence of the metabolic syndrome as well as cut-off points for waist circumference (WC) for diagnosis of MES in Zahedan, southeast Iran. Methods: Totally, 1802 people (735 men and 1067 women) with metabolic syndrome were surveyed according to National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and the International Diabetes Federation (IDF) criteria as well as obtained WC cut-off points for IDF criteria.  Results: The prevalence of metabolic syndrome was higher in women than in men. In both sexes the prevalence increased with age. The prevalence of metabolic syndrome among 1802 individuals aged ≥19 years according to NCEP ATP III,  IDF and IDF -AHA/NHLBI were 21.0% (15.4% in male, 24.9% female), 24.8 (20.0% in male, 28.1% in female) and 23.3% (19.7% in male, 25.8% in female), respectively. Low HDL-C (60.6%) and high WC (43.3%) were the most common components of the metabolic syndrome, followed by high triglycerides (32%), elevated glucose (17.1%) and high blood pressure (13%). Conclusion: Our data shows a high prevalence of MES in Zahedan, Southeast Iran, therefore, future health prevention strategies are required for the prevention of MES.